2023
DOI: 10.1002/anie.202212224
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Kinetics Support a Second Coordination Sphere Mechanism in Metal‐Based Formate Dehydrogenase

Abstract: Metal‐based formate dehydrogenases are molybdenum or tungsten‐dependent enzymes that catalyze the interconversion between formate and CO2. According to the current consensus, the metal ion of the catalytic center in its active form is coordinated by 6 S (or 5 S and 1 Se) atoms, leaving no free coordination sites to which formate could bind to the metal. Some authors have proposed that one of the active site ligands decoordinates during turnover to allow formate binding. Another proposal is that the oxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, the Mo V active site constitutes an intermediate state after product release and one electron oxidation in which the amino acid ligand is quite likely to rebind again to the molybdenum atom which otherwise would be coordinatively unsaturated [ 18 , 49 ]. In previous studies, several groups proposed a hydride transfer mechanism with the formate being bound within the second coordination sphere of the active site metal [ 15 , 50 ]. One of the arguments used by the authors to support their mechanism was that the second p K a value of formic acid (i.e., the one for C-H dissociation) disfavors a proton abstraction and the resulting carbanion would be unstable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Mo V active site constitutes an intermediate state after product release and one electron oxidation in which the amino acid ligand is quite likely to rebind again to the molybdenum atom which otherwise would be coordinatively unsaturated [ 18 , 49 ]. In previous studies, several groups proposed a hydride transfer mechanism with the formate being bound within the second coordination sphere of the active site metal [ 15 , 50 ]. One of the arguments used by the authors to support their mechanism was that the second p K a value of formic acid (i.e., the one for C-H dissociation) disfavors a proton abstraction and the resulting carbanion would be unstable.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 At issue is whether CO 2 (eq 1) or HCO 3 − (eq 3) is the immediate product of enzymatic formate oxidation. 13,14 There are also structural studies that have revealed alternative active site structures to those shown in Figure 1 where dissociation of the protein ligand has occurred, at least under reducing conditions and dependent on the reductant. 15,16 Regardless of the specific chemical mechanism, the reversible catalytic oxidation of formate/reduction of CO 2 continues to receive the attention of researchers across diverse fields due to its relevance to global warming and also to future energy storage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The physiological function of all formate dehydrogenases is the two-electron oxidation of formate (HCOO – ) to carbon dioxide (CO 2 ) (eq ) using various electron acceptors including NAD(P) + , cytochromes, quinones, and Fe–S proteins to mention but a few. ,, It has emerged that most, if not all, formate dehydrogenases are in fact bidirectional and may catalyze the reverse reduction of CO 2 to HCOO – . , The preponderance of evidence is that the reaction occurs via hydride transfer from the C–H group of formate to form CO 2 directly , consistent with the earlier conclusion that CO 2 is the direct product of the reaction and that the reaction occurs without oxygen atom transfer. Still, mechanisms involving oxygen atom transfer have been proposed. , At issue is whether CO 2 (eq ) or HCO 3 – (eq ) is the immediate product of enzymatic formate oxidation. , There are also structural studies that have revealed alternative active site structures to those shown in Figure where dissociation of the protein ligand has occurred, at least under reducing conditions and dependent on the reductant. , Regardless of the specific chemical mechanism, the reversible catalytic oxidation of formate/reduction of CO 2 continues to receive the attention of researchers across diverse fields due to its relevance to global warming and also to future energy storage HCOO CO 2 + H + + 2 e CO 2 + H 2 O normalHCO 3 + H + …”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical measurement can be used to monitor variations of turnover frequency under various experimental conditions (electrode potential, pH, substrate/product concentration) [1] , [2] , [3] , [4] , [5] , or as a function of time when the enzyme inactivates or reactivates following exposure to inhibitors or changes in potential [6] . These variations can be interpreted quantitatively to yield mechanistic information [7] . However, most of the studies focus on the interpretation of relative variations of current, since it is difficult to determine the absolute value of the turnover frequency of an immobilized enzyme.…”
mentioning
confidence: 99%